Integrated Model of Protecting Children's Rights in The Context of Digital Transformation (International Journal of Scientific Trends, 2026)
This article examines the issues of protecting children’s rights and ensuring legal security in the context of digital transformation in Uzbekistan. The study analyzes the impact of digital technologies on children’s rights, including cyberbullying, harmful online content, violations of personal data privacy, and digital safety challenges. International experiences and national legislation are comparatively studied to identify existing legal and institutional problems in the field. The research substantiates the necessity of integrating legal guarantees with legal education mechanisms in order to effectively protect children in the digital environment. Based on the analysis, an integrated model combining state policy, educational institutions, family, law enforcement agencies, digital platforms, and civil society institutions is proposed. The article emphasizes that strengthening digital literacy and legal awareness among children, parents, and teachers is an essential component of ensuring children’s rights in the digital age. The findings of the study may contribute to improving national legislation and developing preventive mechanisms for children’s digital safety.